Lattice location and optical activation of rare earth implanted GaN - Wahl, U.
This paper reviews the current knowledge on rare earths (REs) implanted into GaN with a special focus on their lattice location and on the optical activation by means of thermal annealing. While emission channeling experiments have given information on the lattice location of rare earths following low-dose (≈1013cm-2) implantation, both in the as-implanted state and after annealing up to 900°C, the lattice location of higher-dose implants (1014-1015cm-2) and their defect annealing behaviour were studied using the Rutherford backscattering/channeling (RBS/C) method. The available channeling and luminescence results suggest that the optical activation of implanted REs in GaN is related to their incorporation in substitutional Ga sites combined with the effective removal of the implantation damage